2022
DOI: 10.1002/pbc.29574
|View full text |Cite
|
Sign up to set email alerts
|

Bladder function after conservative surgery and high‐dose rate brachytherapy for bladder–prostate rhabdomyosarcoma

Abstract: Background: Conservative surgery (CS) brachytherapy (BT) techniques for local therapy in bladder-prostate rhabdomyosarcoma (BP-RMS) seek to retain organ function. We report bladder function after high-dose rate (HDR) BT combined with targeted CS for any vesical component of BP-RMS. Procedure:Prospective cohort of all BP-RMS patients between 2014 and 2019 receiving HDR-BT (iridium-192, 27.5 Gy in five fractions) with/without percutaneous endoscopic polypectomy (PEP) or partial cystectomy (PC). Functional asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The variation of the median values was not significant (p = 0.41, Kruskal-Wallis test). There was no significant difference between the two groups (graphs not shown) findings were not provided in detail (Arndt et al 2004;Lobo et al 2022;Martelli et al 2009;Stenman et al 2022), except in one study (Martelli et al 2016).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The variation of the median values was not significant (p = 0.41, Kruskal-Wallis test). There was no significant difference between the two groups (graphs not shown) findings were not provided in detail (Arndt et al 2004;Lobo et al 2022;Martelli et al 2009;Stenman et al 2022), except in one study (Martelli et al 2016).…”
Section: Discussionmentioning
confidence: 89%
“…Simultaneously, this case emphasizes the importance of timely local therapy. Other studies with longer postoperative follow-up times but smaller study cohorts reported 100% EFS rates after BT in BP-RMS patients (Lobo et al 2022 ; Stenman et al 2022 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…rare disease, there is significant bladder-related morbidity and bladder dysfunction. [1][2][3][4] In this issue of The Journal, Wang et al (page 1202) report that with robust follow-up patients with a more aggressive radical surgery had an improved quality of life than those patients treated with less aggressive upfront initial resection. 5 With increasing survival for some malignancies, it is crucial to involve specialists who will be managing the long-term sequelae of initial therapy from a given organ when developing a treatment plan with the family.…”
mentioning
confidence: 99%
“…Even in relatively shorter-term follow-up for this rare disease, there is significant bladder-related morbidity and bladder dysfunction. 1-4 In this issue of The Journal, Wang et al (page 1202) report that with robust follow-up patients with a more aggressive radical surgery had an improved quality of life than those patients treated with less aggressive up-front initial resection. 5…”
mentioning
confidence: 99%